2006
DOI: 10.1289/ehp.9146
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Pesticide Use and Hypospadias in Eastern Arkansas

Abstract: IntroductionWe assessed the relationship between hypospadias and proximity to agricultural pesticide applications using a GIS-based exposure method.MethodsWe obtained information for 354 cases of hypospadias born between 1998 and 2002 in eastern Arkansas; 727 controls were selected from birth certificates. We classified exposure on pounds of pesticides (estimated by crop type) applied or persisting within 500 m of each subject’s home during gestational weeks 6 to 16. We restricted our analyses to 38 pesticides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 56 publications
4
52
1
5
Order By: Relevance
“…Pada penelitian lain melaporkan paparan pestisida dalam radius 2600 feet atau 780 meter dapat menyebabkan cedera ditingkat sel. Apabila ibu hamil terpapar pestisida dalam kurun waktu 3 bulan terutama rentang usia kehamilan 6 sampai 16 minggu maka perkembangan janin dapat terpengaruh sampai kepada timbulnya penyakit keganasan.. 10,12 Kelebihan penelitian kami adalah setelah dilakukan pencarian dari literatur jurnal PUBMED, penelitian ini yang pertama kali menggunakan perasat Google Earth dalam melihat lokasi tempat tinggal dekat dengan areal persawahan.…”
Section: Pembahasanunclassified
“…Pada penelitian lain melaporkan paparan pestisida dalam radius 2600 feet atau 780 meter dapat menyebabkan cedera ditingkat sel. Apabila ibu hamil terpapar pestisida dalam kurun waktu 3 bulan terutama rentang usia kehamilan 6 sampai 16 minggu maka perkembangan janin dapat terpengaruh sampai kepada timbulnya penyakit keganasan.. 10,12 Kelebihan penelitian kami adalah setelah dilakukan pencarian dari literatur jurnal PUBMED, penelitian ini yang pertama kali menggunakan perasat Google Earth dalam melihat lokasi tempat tinggal dekat dengan areal persawahan.…”
Section: Pembahasanunclassified
“…47 Outro estudo destaca a relação entre agrotó-xicos específicos e MFC específicas: anencefalia foi relacionada a 2,4-D, metomil, imidacloprida e ao éster fosfato α-(para-nonil fenol)-ω-hidroxi polioxietileno; espinha bífida a bromoxinil e a fenda labial e palatina a trifluralina e maneb. 48 A terceira maior associação encontrada entre as mesorregiões analisadas foi referente à "Outras malformações do aparelho geniturinário" (OR = 1,62, IC 95% = 1,28 -2,06), similar aos achados de Meyer e colaboradores 49 que encontraram associação positiva entre a exposição à agrotóxicos específicos e hipospadia, um tipo de MFC do aparelho geniturinário masculino. Foram analisados 38 agrotóxicos que possuíam efeitos estrogênicos ou antiandrogênicos e outros com alguma evidência de toxicidade para a reprodução/desenvolvimento.…”
Section: Resultsunclassified
“…[16][17][18][19][20] We are aware of 1 other study that examined residential proximity to agriculture-related pesticide applications. 22 It too did not find an association with specific chemical exposures, but its exposures were derived from annual statewide summaries of applications to specific crop types.…”
Section: Discussionmentioning
confidence: 96%
“…12 Three subsequent large maternal occupation-based studies have not suggested elevated risk. [13][14][15] Studies examining maternal serum levels of persistent pesticides DDE [16][17][18][19][20] and chlordane 21 and 1 study that estimated exposure based on residential proximity to certain crops 22 also do not provide evidence for association. These studies are limited by relatively crude measures of exposure, small sample sizes, or investigation of a limited set of specific compounds.…”
mentioning
confidence: 99%